Menumbuhkan Rasa Percaya Diri Anak dengan Motivasi dan Apresiasi - Egidia Putri; Agus Suriadi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Self-confidence is an important basic thing in carrying out various activities in life. Confidence is also needed in the teaching and learning process where when learning sometimes someone needs guidance and direction from others. But sometimes someone is afraid to ask questions when experiencing difficulties that make some one entangled in ignorance. This is also what is faced by a child at the Menara Kasih Indonesia Orphanage Foundation where the child lacks confidence in his ability in terms of learning. Through this case, one of the efforts made is to carry out mini project activities using the case work method through stages consisting of: of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The process of solving client problems is applied by a motivation and appreciation system as a strategy to increase the client's interest in learning. The purpose of implementing this program is to increase the confidence in children and enthusiasm in learning and trying new things.